Strategies at SD Muhammadiyah 3 Pandaan in Optimizing Al-Islamic Learning and Kemuhammadiyahan During the Covid-19 Pandemic - Ovi Shinta Asri; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study was conducted to determine the Al-Islam and Kemuhammadiyahan learning strategies in the midst of the COVID-19 pandemic situation which required online learning. In collecting data for this scientific work using methods in the form of interviews and observations during the research process. This study aims to find out how the strategies applied by SD Muhammadiyah 3 Pandaan in learning Al-Islam and Kemuhammadiyahan during online learning take place. The results show that in implementing learning strategies in the midst of a pandemic, SD Muhammadiyah 3 Pandaan school provides fun online learning that does not pressure students so that students feel happy in learning. In learning Al-Islam and Kemuhammadiyahan SD Muhammadiyah 3 Pandaan managed to package memorable online learning by utilizing technological advances such as learning through live streaming, google meet, and learning videos. In the teaching and learning process of Al-Islam and Kemuhammadiyahan learning, the school, especially Al-Islam and Kemuhammadiyahan teachers, also applies rote learning as well as Al-Islam and Kemuhammadiyahan learning when the learning is face to face directly. The difference is when online learning is for memorizing students learn and submit their assignments in the form of videos that are sent to the teacher. The results of the study, Al-Islam and Kemuhammadiyahan teachers more often apply learning through videos containing subject matter so that students can access it freely without being bound by time. The success of online learning at SD Muhammadiyah 3 Pandaan is due to the role of teachers and students who can support each other for communication to continue so that there is reciprocity in the learning process even though distance learning.